A comparison between North and South business ethics: the concepts of Renzhi and Fazhi in China. Issue 5 (20th October 2018) - Rawwas, Mohammed Y. A.; Wang, Yanfang; Zhao, Baochun; Javed, Basharat
ABSTRACT: The purpose of this study is to compare the ethical standards of business practitioners of Northern provinces of the People's Republic of China (PRC) who follow the 'rule by man' (i.e. the Renzhi system) versus those of southern provinces who follow the 'rule by law' (i.e. the Fazhi system). Our Shanghai survey represented the south Chinese sample, and our Shijiazhuang mailing represented our north Chinese sample. We received 95 completed responses for the former and 102 completed responses for the latter. Our results found that the south Chinese practitioners were more likely to be idealistic, possessed virtue epistemic traits and were more sensitive to ethical practices than north Chinese practitioners were.